Concentração de resveratrol e expressão de resveratrol sintase em espécies de Arichis - Carvalho, Paula Andréa Sampaio de Vasconcelos [UNESP] (2013)
Resveratrol is a phytoalexin produced under biotic and abiotic stresses. It has been found in a restricted number of plant species including peanut (Arachis hypogaea) and its wild relatives. This phytochemical has antioxidant properties, being considered a promising antitumour, cardioprotective and neuroprotective agent. Peanut is an allotetraploid specie with an AABB genomic constitution. Arachis ipaënsis and A. duranensis are the donors of the B genome and the A genome, respectively. Previous studies have shown that wild species of the genus Arachis can produce resveratrol. Therefore, the evaluation of other species of thus genus and the analysis of the variation in the production of resveratrol between accessions is essential for better exploitation of wild species in the genus Arachis. It also important the understanding of the variation in resveratrol concentration between species and accessions and that could be reached through the better understating of the role resveratrol synthase.. . The aims of this work were to evaluate the variation in resveratrol production between species (A. hypogaea, A. stenosperma, A. valida, A. wiliamsii, A. duranensis, A. ipaënsis and in a synthetic amphidiploid derived from these two wild species A. duranensis and A. ipaënsis) and between accessions of the same specie (A. hypogaea and A. stenosperma) through HPLC, and to quantify the expression of resveratrol synthase by RT-qPCR in A. hypogaea, A. duranensis, A. ipaënsis and in a synthetic amphidiploid. Leaves for the test and control groups were collected from plants cultivated in a greenhouse and three biological replicates were evaluated for each specie. The synthesis of resveratrol in leaves was induced by treatment with UV for 2 hours and thirty minutes and then the difference in the concentration of resveratrol between species and between the accessions and cultivars of the same species was analyzed. We found new ...